Um estudo de Proechimys (Rodentia, Echimyidae) do Amapá - Lara, Marcia C. (1986)
Proechimys cuvieri with a caryotype of 2N = 28 from Amapá Territory was studied comparatively with a sample from the same location. The morphometric univariate and multivariate analysis done for the samples showed an ocurrence of another morphospecies in the region. The study indicates the necessity of the separation in age classes for the comprehension of the morphology and systematics of this taxon. The two species seems to complete the morphogenesis before it accomplishes their final size.